2015
DOI: 10.1007/s11340-015-0069-2
|View full text |Cite
|
Sign up to set email alerts
|

In-Situ Measurements of Free-Standing, Ultra-Thin Film Cracking in Bending

Abstract: Metallic thin films are widely used and relied upon for various technologies. Direct measurements of fracture toughness are rare for metallic thin films and existing methods for obtaining these measurements often do not provide characterization of the cracking process for determination of crack growth mechanisms. To rectify this, we explore a new technique which utilizes doubly clamped, in-situ three-point bend testing of micro-scale and nano-scale specimens. This is done by in-situ scanning electron microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…210 As all of these were in compression and fracture instabilities are generally associated with silicon in tension, the role of length scale is not totally addressed by these experiments. In a study of prenotched, bending fracture in an iron alloy just published, 217 ductile crack growth was observed in 100, 500, and 2500 nm thick beams under threepoint bending conditions. We have since applied this to h110i-oriented silicon beams.…”
Section: -14 Gerberich Et Almentioning
confidence: 97%
“…210 As all of these were in compression and fracture instabilities are generally associated with silicon in tension, the role of length scale is not totally addressed by these experiments. In a study of prenotched, bending fracture in an iron alloy just published, 217 ductile crack growth was observed in 100, 500, and 2500 nm thick beams under threepoint bending conditions. We have since applied this to h110i-oriented silicon beams.…”
Section: -14 Gerberich Et Almentioning
confidence: 97%
“…The in situ single point bending test can also be used in the bending of nanoscale materials; for example, Vlassov et al [ 50 ] measured Young's modulus and yield point of the Ag nanowires and even observed their plastically deformation before fracture. With the aim of providing the characterization of cracking process of metallic thin films, Hintsala et al [ 51 ] reported the in situ doubly clamped three-point bending test of microscale and nanoscale specimens. The crack tip behavior was not kept out of view by the indenter as usual, allowing for further EBSD characterization.…”
Section: In Situ Sem Mechanical Tests Of Micro/nanomaterialsmentioning
confidence: 99%
“…To promote these studies, advanced small-scale mechanical testing methods are used, which can isolate features of interest in the sample and measure them separately. For example, increased plasticity and strength was demonstrated by compression of nanometric metallic pillars [ 1 , 2 , 3 , 4 , 5 , 6 ], tension of nanowires and films [ 7 , 8 , 9 , 10 ], and bending of microbeams [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%